Careers Making Committees Work. - Selinger, C.
This paper presents some ways of improving the effectiveness and satisfaction of working on a committee. In a properly run committee, you have the opportunity to learn management skills and make contacts that can boost your career, and get something done as well
Keywords: Career enhancement; Committee; Management skills; Satisfaction